1992
DOI: 10.1007/bf01082445
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cell proliferation in gastric carcinoma: comparative analysis of Ki-67 and proliferative cell nuclear antigen (PCNA)

Abstract: Immunostaining to identify nuclear antigens expressed throughout the cell cycle provides a convenient way of assessing proliferating kinetics in tumours. We studied proliferation activity of gastric carcinomas by Ki-67 and PCNA immunostaining and the two methods were compared. The mode of tissue preparation differed, fresh frozen for Ki-67 and formalin-fixed paraffin-embedded for PCNA. Immunostaining with avidin-biotin was used in both. The labelling index (LI) and a semi-quantitative grading of cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
3
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
2
21
3
3
Order By: Relevance
“…The absence of a correlation between PCNA expression and BrdU incorporation in certain organs was in agreement with a number of previous reports in which no correlation was observed between anti-PCNA LI and other indices of proliferation (Jain et al, 1991;Yu et al, 1991;Leonardi et al, 1992;Rosa et al, 1992;Visakorpi, 1992).…”
Section: Discussionsupporting
confidence: 81%
“…The absence of a correlation between PCNA expression and BrdU incorporation in certain organs was in agreement with a number of previous reports in which no correlation was observed between anti-PCNA LI and other indices of proliferation (Jain et al, 1991;Yu et al, 1991;Leonardi et al, 1992;Rosa et al, 1992;Visakorpi, 1992).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, Rosa et al found no correlation between the two indices, PCNA and Ki-67. 35 PCNA expression associated with DNA synthesis also is dependent on other factors; e.g., its synthesis can be induced by various growth factors. 36,37 Therefore, our findings may reflect not only the correlation between proliferative activity and p21 expression but also the fact that p21 interacts with PCNA and inhibits its action.…”
Section: Discussionmentioning
confidence: 99%
“…4 2 -4 6 Particularly, the PCNA index showed a good correlation with the Ki-67 (MIB-1) index that is widely used to estimate proliferative activity in formalin-fixed paraffin-embedded tissues. [44][45][46] Some studies showed a lack of correlation between PCNA and Ki-67 indexes 20,47 that was attributed to several factors, including intertumoral and intratumoral heterogeneity, deregulated expression of PCNA, and prolonged half-life of PCNA leading to its persistence in some cells that are not actively dividing. 17,47 For the AgNOR count, it was shown that the mean AgNOR count differentiated between benign and malignant ovarian tumors but was of limited value in differentiating between borderline and malignant ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%